(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
Transglobal leadership in the digital era in addition to carrying out its duties in institutions also pays attention to health procedures and digital progress. This is a big challenge because the adaptation process is certainly not as easy as turning your palm. This adaptation process will be successful if leaders with global leadership can transform, pay attention to situations and conditions properly and can improve leadership competence in the digital era.